Tensor Product of Linear Transformations
📂Linear AlgebraTensor Product of Linear Transformations
Buildup
Given finite-dimensional vector spaces V1,V2,W1,W2 and linear transformations ϕ1:V1→W1, ϕ2:V2→W2, one can consider the following bilinear transformation.
V1×V2→W1⊗W2
(v1,v2)↦ϕ1(v1)⊗ϕ2(v2)
ϕ1,ϕ2 is a linear transformation, and it is easy to see that this function is bilinear due to the definition of product vectors.
ϕ1(αv1+βv1′)⊗ϕ2(v2)=(αϕ1(v1)+βϕ1(v1′))⊗ϕ2(v2)=αϕ1(v1)⊗ϕ2(v2)+βϕ1(v1′)⊗ϕ2(v2)
ϕ1(v1)⊗ϕ2(αw1+βw1′)=ϕ1(v1)⊗(αϕ2(w1)+βϕ2(w1′))=αϕ1(v1)⊗ϕ2(w1)+βϕ1(v1)⊗ϕ2(w1′)
Universality of the tensor product
For vector spaces V1,…,Vr and W, suppose we have the following multilinear transformation ϕ given.
ϕ:V1×⋯×Vr→W
Then, there exists a unique linear transformation ψ satisfying the following.
ψ:V1⊗⋯⊗Vr→W
ϕ(v1,…,vr)=ψ(v1⊗⋯⊗vr),∀vi∈Vi,∀i
Then, according to the theorem above, a unique linear transformation V1⊗V2→W1⊗W2 exists.
Definition
The tensor product of two linear transformations ϕ1:V1→W1 and ϕ2:V2→W2 ϕ1⊗ϕ2 is defined as follows.
ϕ1⊗ϕ2:V1⊗V2(v1⊗v2)→W1⊗W2↦ϕ1(v1)⊗ϕ2(v2),∀v1∈V1,∀v2∈V2
(ϕ1⊗ϕ2)(v1⊗v2)=ϕ1(v1)⊗ϕ2(v2)
Generalization
Regarding 1≤i≤n, the tensor product of linear transformations ϕi:Vi→Wi is the unique linear transformation satisfying the following.
ϕ1⊗⋯⊗ϕn:V1⊗⋯⊗Vn→W1⊗⋯⊗Wn
(ϕ1⊗⋯⊗ϕn)(v1⊗⋯⊗vn)=ϕ1(v1)⊗⋯⊗ϕn(vn),∀vi∈Vi
Properties
For linear operators ϕ1,ϕ2:V→V and ψ1,ψ2:W→W, the composition of two tensor products (ϕ1⊗ψ1) and (ϕ2⊗ψ2) is as follows.
(ϕ1⊗ψ1)∘(ϕ2⊗ψ2)=(ϕ1∘ϕ2)⊗(ψ1∘ψ2)
Generalization
ϕ1⊗⋯⊗(αϕk+βψk)⊗⋯⊗ϕn=α(ϕ1⊗⋯⊗ϕk⊗⋯⊗ϕn)+β(ϕ1⊗⋯⊗ψk⊗⋯⊗ϕn)
(ϕ1⊗⋯⊗ϕn)∘(ψ1⊗⋯⊗ψn)=(ϕ1∘ψ1)⊗⋯⊗(ϕn∘ψn)
Proof
Linearity
It can easily be shown using the definition (1) and the definition of product vectors. For ϕ:V→V′, ψ1,ψ2:W→W′, and v∈V,w∈W,
[ϕ⊗(αψ1+βψ2)](v⊗w)=ϕ(v)⊗[(αψ1+βψ2)(w)]=ϕ(v)⊗[αψ1(w)+βψ2(w)]=α[ϕ(v)⊗ψ1(w)]+β[ϕ(v)⊗ψ2(w)]=[α(ϕ⊗ψ1)](v⊗w)+[β(ϕ⊗ψ2)](v⊗w)=[α(ϕ⊗ψ1)+β(ϕ⊗ψ2)](v⊗w)
⟹ϕ⊗(αψ1+βψ2)=α(ϕ⊗ψ1)+β(ϕ⊗ψ2)
■
Composition
The calculation can easily be done using the definition (1) and the definition of product vectors. For v∈V and w∈W,
[(ϕ2⊗ψ2)∘(ϕ1⊗ψ1)](v⊗w)=(ϕ2⊗ψ2)[(ϕ1⊗ψ1)(v⊗w)]=(ϕ2⊗ψ2)(ϕ1(v)⊗ψ1(w))=[ϕ2(ϕ1(v))]⊗[ψ2(ψ1(w))]=[(ϕ2∘ϕ1)(v)]⊗[(ψ2∘ψ1)(w)]=[(ϕ2∘ϕ1)⊗(ψ2∘ψ1)](v⊗w)
⟹(ϕ2⊗ψ2)∘(ϕ1⊗ψ1)=(ϕ2∘ϕ1)⊗(ψ2∘ψ1)
■